Autoimmune mastitis as a clinical manifestation of Behçet’s disease: a case report and a systematic literature review - G. Conti; M. Materazzo; G. Vanni; M. Pellicciaro; A. Granai; A. De Majo; F. Tacconi; J. Caspi; M. Dauri; O. Buonomo (World Cancer Research Journal, 2023)
Objective: Behçet’s disease (BD) is a rare autoimmune disorder of unknown origin that causes chronic and systemic inflammation in blood vessels. The condition is traditionally defined by oral and genital ulcers and uveitis; however, cutaneous, articular, neurologic, vascular, gastrointestinal, and pulmonary manifestations may also be observed. It is more prevalent throughout the Silk Road, such the Mediterranean basin and the East Asia. There have been reported only four cases of BD targeting the breast. We herein present a case report of an autoimmune mastitis (AM) in a 23-year-old patient diagnosed for BD treated surgically. Case Presentation: The patient is a 23-year-old Italian female who reported recurrent aphthous ulcers of the oral mucosa, occasional vaginal dryness, and genital lesions, diagnosed for BD according to the International Study Group (ISG) criteria and the skin biopsy. The patient referred to our department for examination of a painful and ulcerating lump at the 5 o’clock position of the right breast, which had been present for one month. Results: In our case, we opted for a surgical approach, which proved to be effective in treating the lesion. Considering the relapsing and remitting nature of BD, surgical intervention is questionable when compared to appropriate conservative treatment. Conclusions: A conservative approach should be evaluated first, in order to have regard to the recurrent course of the disease and to the risk that numerous surgical procedures may result in irreversible aesthetic damage.